The popstar's wedding - "Mitchelhill, Barbara " (London; Andersen Press Ltd, 2018)
Damian Drooth, the one-of-a-kind detective hero, is back. Criminals beware! A superstar singer, Tiger Lilly, is getting married to a footballer. Who better to guard her fabulous wedding pressents than her number one fan, the genius private eye Damian Drooth? Will Damian's amazing brain power and cunning plans be enough to track down some notorious crooks among the wedding guests and win Tiger Lilly's undying admiration? Packed with rib-tickling pictures from Tony Ross, this is perfect for newly confident young readers of 6 and up!
Donated from "Book Planet", Dated 18-4-2025.
Keywords: Child detectives